Impact of Mismatched Detector-Blur Models on (67)Ga SPECT Tumor Detection - Gifford, H. C. (2007)
The quality of SPECT images suffers from the effects of photon attenuation and scatter, and from distance-dependent collimator blur, and many researchers have shown the benefit of compensating for these degradations in the inverse problem. For this work, we examined how using an incorrect collimator-blur model affects the detection and localization of (67)Ga-avid lymphomas in simulated chest scans. In particular, we considered whether blur-overcompensation can enhance reconstructed images for purposes of localizing tumors. Variations in the correct linear model for medium-energy, parallel-hole collimators were compared by means of LROC studies with human and localizing model observers. Imaging data consisted of Simind projections of the MCAT phantom, and RBI reconstructions were performed. Our results indicate that tumor-detection performance is not improved by using a mismatched RC model. Reconstruction with increased RC requires more iterations, which leads to longer noise correlations. Our results also suggest a substantial observer insensitivity to the accuracy of the RC model.